Analisis Kelayakan Finansial Usahatani Jeruk Siam (Citrus nobilis Lour.) Pada Usaha Yakin Maju Desa Pulau Jambu Kecamatan Kuok Kabupaten Kampar - Ria Mardalena; Yusmini Yusmini; Susy Edwina (Jurnal Sosial Ekonomi Pertanian, 2022)
This study aims to analyze the financial feasibility and sensitivity to price changes of the input and output of siamese orange Usaha Yakin Maju farming in Pulau Jambu Village Kuok District Kampar Regency. Usaha Yakin Maju is one of the farms that has been cultivating siamese orange since 2009 until now. This research uses the case study method. Reaserch data consist of primary data and secondary data. Data analysis was perfomed using four investment criteria, namely Net Present Value (NPV), Net Benefit Cost Ratio (Net B/C), Internal Rate of Return (IRR) and Payback Period (PP). The results showed that business activities carried out by Usaha Yakin Maju were financially feasible, indicated by a positive business NPV value of Rp.8.185.854.454,-, the Net B/C value is greater than one, which is 6,29, the IRR value is greater than the Social Opportunity Cost of Capital (SOCC) is 43,73%, and the Paybak Period value is smaller than the age of the business, which is 4 years 9 months. The results of the sensitivity analysis to the increase in pesticide prices by 10%, a decrease in prices of Siamese oranges by 20%, and a decrease in the number of Siamese citrus production by 20% will reduce NPV, IRR, Net B/C, and PP but remain at the same level acceptable, indicate that this business is still financially feasible.